2008
DOI: 10.4049/jimmunol.181.4.2878
|View full text |Cite
|
Sign up to set email alerts
|

CpG Methylation of the IFNG Gene as a Mechanism to Induce Immunosupression in Tumor-Infiltrating Lymphocytes

Abstract: The execution of appropriate gene expression patterns during immune responses is of eminent importance where CpG methylation has emerged as an essential mechanism for gene silencing. We have charted the methylation status of regulatory elements in the human IFNG gene encoding the signature cytokine of the Th1 response. Surprisingly, human naive CD4+ T lymphocytes displayed hypermethylation at the IFNG promoter region, which is in sharp contrast to the completely demethylated status of this region in mice. Th1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 28 publications
(52 reference statements)
2
52
0
Order By: Relevance
“…In particular, IFN-g production by tumorspecific T cells is shown to be inhibited in tumor-bearing hosts (7,15,17). This is consistent with the epigenetic silencing of ifng gene in tumor-infiltrating CD4 þ effector T cells (24). Moreover, a positive correlation between the survival of patients with cancer and the mRNA expression of T-helper cell (T H 1)-associated markers such as IFN-g and T-box expressed in T cells (T-bet) in tumor tissues has been observed (25).…”
Section: Introductionsupporting
confidence: 74%
“…In particular, IFN-g production by tumorspecific T cells is shown to be inhibited in tumor-bearing hosts (7,15,17). This is consistent with the epigenetic silencing of ifng gene in tumor-infiltrating CD4 þ effector T cells (24). Moreover, a positive correlation between the survival of patients with cancer and the mRNA expression of T-helper cell (T H 1)-associated markers such as IFN-g and T-box expressed in T cells (T-bet) in tumor tissues has been observed (25).…”
Section: Introductionsupporting
confidence: 74%
“…Naive T cell differentiation into Th1 or Th2 effector cells was performed as described previously (13). Th17 differentiation was conducted in serumfree AIM-V medium (Life Technologies) supplemented with 5 ng/ml TGFb, 20 ng/ml IL-6, 10 ng/mL IL-1b, 10 ng/ml IL-23, 25 ng/ml IL-21, 25 U/ ml IL-2, 5 mg/ml anti-IFN-g, 1 mg/ml anti-CD28, and 3 mg/ml platebound anti-CD3.…”
Section: Cell Culturingmentioning
confidence: 99%
“…Locus-specific PCR amplification and snapshot reaction DNA bisulfite conversion was performed as described previously (10,13). Locus-specific PCR primers (Cybergene, Stockholm, Sweden) were designed for the FOXP3, IFNG, and IL-17 loci (Table I).…”
Section: Cd4mentioning
confidence: 99%
“…Thus, it is possible that DAC can reverse PTEN silencing and halt the progression of breast cancer by increasing PTEN expression. Janson et al (2008) found increased expression of IFN-γ in 5-Aza-treated tumorinfiltrating lymphocytes, suggesting that DNMT inhibitors may stimulate the immune response in the TME. Most studies have described the effect of DNMT inhibitors on stromal cells in vitro.…”
Section: Epigenetic Therapy Targets Stromal Cells In the Tumor Microementioning
confidence: 86%
“…Janson et al (2008) demonstrated the different methylation status of the interferon-γ (IFN-γ) gene promoter and upstream enhancer in naive CD4 + T lymphocytes. However, the IFN-γ gene promoter and enhancer were demethylated in Th1 lymphocytes, where the expression of IFN-γ was induced.…”
Section: Dna Methylation In Immune Cellsmentioning
confidence: 99%